Receptors Mediating Host-Microbiota Communication in the Metaorganism: The Invertebrate Perspective - Dierking, Katja; Pita, Lucía (Frontiers in Immunology, 2020)
Multicellular organisms live in close association with a plethora of microorganism, which have a profound effect on multiple host functions. As such, the microbiota and its host form an intimate functional entity, termed the metaorganism or holobiont. But how does the metaorganism communicate? Which receptors recognize microbial signals, mediate the effect of the microbiota on host physiology or regulate microbiota composition and homeostasis? In this review we provide an overview on the function of different receptor classes in host-microbiota communication throughout the animal kingdom. We put a special focus on invertebrate hosts, including both traditional invertebrate models such as Drosophila melanogaster and Caenorhabditis elegans and ‘non-model’ invertebrates in microbiota research. Finally, we highlight the potential of invertebrate systems in studying mechanism of host-microbiota interactions.